A COMPARATIVE STUDY OF INTRATHECAL DEXMEDETOMIDINE 10mcg AND FENTANYL 25mcg AS ADJUVANTS TO 0.5% HYPERBARIC BUPIVACAINE IN SPINAL ANAESTHESIA WITH A 0.5ML NORMAL SALINE CONTROL GROUP - Dr. Bhagyalakshmi.M, Dr. Dharuni Priya Krishnappa Ramdass, Dr. Roopa Rani. K (South Eastern European Journal of Public Health, 2025)
Background: Spinal anesthesia provides effective anesthesia for lower abdominal and limb surgeries. Adjuvants can enhance onset, duration, and postoperative analgesia, improving surgical conditions and patient satisfaction.Objective: To compare intrathecal dexmedetomidine (10 µg) and fentanyl (25 µg), each combined with 0.5% hyperbaric bupivacaine, against a saline control for block characteristics, analgesic duration, and safety in adult patients.Methods: A randomized trial included 90 ASA I–II patients (18–60 years) for lower abdominal and lower limb surgeries. They were divided into three groups (n=30): Group C (bupivacaine + saline), Group D (bupivacaine + 10 µg dexmedetomidine), and Group F (bupivacaine + 25 µg fentanyl). Primary outcomes were sensory/motor onset, block duration, and analgesia. Hemodynamic stability was routinely monitored and assessed.Results: In Group D, onset of sensory block (244±70.31 s) was faster than in Group F (283.17±47.61 s) and Group C (343.33±53.52 s), p<0.001. Similarly, motor block onset in Group D (300.67±61.40 s) was quicker than Group F (370.33±64.67 s) and Group C (400.67±55.64 s), p<0.001. Two-segment sensory regression was longest in Group D (168.5±20.68 min), vs. Group F (103.23±8.82 min) and Group C (87.37±5.88 min), p<0.001. Hemodynamic changes were minimal (p>0.05). Overall, dexmedetomidine prolonged analgesia significantly (470.5±59.8 min) vs. fentanyl (299.5±47.98 min) and control (236.17±20.37 min), p<0.001, with sedation at 15% and vitals. This improvement translated into reduced analgesic requirements and increased patient satisfaction, underscoring dexmedetomidine as an effective adjuvant.Conclusion: Dexmedetomidine improves onset and duration of spinal anesthesia with minimal hemodynamic fluctuations, underscoring its safety, efficacy as an adjuvant for lower abdominal and limb surgeries.